Tempos de festejar: Kerbfest como patrimônio teuto-brasileiro de Seara/SC (1993-2005) - Kuester, Sandra (2020)
This research analyzed the Kerbfest of Seara/SC, between the years 1993 to 2005. The objective was to examine how the Kerbfest built bonds of belonging between the descendants of Germans in the municipality of Seara. The methodology used comprised a bibliographic study that, firstly, contextualized the party through the processes of German colonization at national and municipal levels. Subsequently, ethnic relations were problematized, as well as the notions of representativeness and heritage assets. For the festivity, oral, audiovisual sources, newspapers, minutes from presbytery meetings, photographs and brochures were used. In this way, the study turned to the analysis of representations and ethnic relations and their heritage assets. The main results of this research can be pointed out as a party idealized by a pastor and that, initially, was intended to raise profits for the Evangelical Church of Lutheran Confession in Brazil of Seara/SC. However, the meaning of the party was understood in different ways among its coordinators; but, for everyone on the team, it was a way of representing Germanity, one of the German-Brazilian ethnic characteristics. It also brought an imagined past created based on the customs of the late 19th century in Germany with nationalist ideals and disseminated in Brazil to a large extent in the 1980s by folklorists, in addition to integrating elements from other Kerbfesten in the region. The festival was considered a tradition due to its constant repetition in the municipal and religious calendars of Lutheran confession. For the holding of the Kerbfest, there were ethnic exchanges that started from the sponsorship, participation in the party and in the composition of dishes, selected by the organizers, considered typical of German cuisine. This festivity represented not only an imaginary German past, but also a colonial past in the region, being part of the cultural heritage.